Nab-paclitaxel after docetaxel hypersensitivity reaction: case report and literature review. - Pellegrino, Benedetta; Boggiani, Daniela; Tommasi, Chiara; Palli, Dante; Musolino, Antonino (Acta Biomedica Atenei Parmensis, 2017)
Taxanes, including paclitaxel and docetaxel, are one of the most active cytotoxic agents in breast cancer treatment including Her-2 positive subtype characterized by aggressive clinical and pathological features since the early stage. However, their use is sometimes limited by the occurrence of hypersensivity reactions (HSRs) characterized by erythematous rashes, bronchospasm, respiratory distress, hypotension, and pulmonary edema. Cross-reactions between paclitaxel and docetaxel are described in literature with a rate ranging from 49% to 90%. Abraxane (nab-paclitaxel), an albumin-bound form of paclitaxel, has a different toxicity profile from solvent-based paclitaxel and a lower rate of HSRs. Interestingly, several authors have recently reported cases of patients who developed HSRs to taxanes, principally paclitaxel, and were then safety treated with Abraxane, suggesting the absence of cross-reactivity between these drugs. Based on these considerations, we report our clinical experience and perform a literature review on this topic with the aim to investigate the cross-reactivity between nab-paclitaxel and other taxanes, in particular with docetaxel.